Symbiosis Islands - Ronson, C.; Hynes, M.; Ramsay, Joshua; Sullivan, J. (Elsevier, 2013)
A symbiosis island is a genomic island that confers upon the bacterium carrying it the ability to form a mutualistic relationship with a eukaryotic host. The symbiosis island of Mesorhizobium loti strain R7A is a 501.8-kb chromosomally integrated element that is able to excise and transfer by conjugation to nonsymbiotic mesorhizobia in the environment. The recipients are converted to symbionts able to nodulate and fix nitrogen with Lotus species. The island integrates into a phe-tRNA gene, reconstructing the gene at one (left) end of the island and producing a 17-bp direct repeat of the 3′ end of the tRNA gene at the other end. The island has a mosaic structure suggesting that it evolved in a stepwise fashion via multiple recombination events. It is a member of an emerging class of acquired genetic elements termed ‘integrative and conjugative elements’ that contribute to the diversification and adaptation of bacteria to environmental niches.